Absence of clinical relationship between oxidized low density lipoproteins and diabetic peripheral neuropathy: a case control study - Rosales-Hernandez, Alma; Cheung, Audrey; Podgorny, Peter; Chan, Cynthia; Toth, Cory (Lipids in health and disease, 2014)
The pathophysiology of diabetic peripheral neuropathy (DPN) is complex and uncertain. A potential comorbidity in diabetes mellitus (DM) that may contribute to greater severity of DPN is a lipid disorder, such as with elevated cholesterol, low density lipoproteins or triglycerides. Oxidized low density lipoprotein (oxLDL) is a form of cholesterol that exerts direct toxic effects and contributes to pathogenicity through ligating a receptor called lectin-like receptor (LOX-1). We examined plasma oxLDL levels in cohorts of patients with DPN with neuropathic pain (NeP), DPN patients without NeP, DM patients without DPN, patients with idiopathic peripheral neuropathy, and control subjects without DM or neuropathy. Our outcome measure was extent of oxLDL elevation, measured as fasting with Enzyme-Linked ImmunoSorbant Assay (ELISA) studies. Severity of diabetes was assessed using hemoglobin A1C measurements. Neuropathic severity was measured with the Utah Early Neuropathy Score (UENS). We hypothesized that DPN presence would be associated with oxLDL elevations. A total of 115 subjects (47 with DPN and NeP, 23 with DPN without NeP, 12 with diabetes only, 13 with idiopathic peripheral neuropathy, and 20 control subjects without diabetes or neuropathy) were studied. Duration of diabetes and diabetic glycemic measures were similar between populations with DM. Severity of DPN was similar between cohorts with DPN and NeP and DPN without NeP. Plasma oxLDL levels were similar between all cohorts, without any elevation in the presence of DM noted in any cohort with DM. oxLDL levels are not different in patients with DPN, and their lack of greater presence suggests that any pathogenic role in human DPN is likely limited.